2021
DOI: 10.21873/invivo.12589
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Presentation of a Post-procedural Breast Hematoma: A Case Report

Abstract: Background/Aim: Hematoma is the most frequent complication after Vacuum-Assisted Breast Biopsy (VABB) in 13% of cases. A direct communication channel with patients eases the diagnosis of VABB complications and ensures treatment at an early stage, as outpatients, in most cases. In 2020, due to the COVID-19 pandemic, we observed a reduction of self-reported postoperative complication leading to delay in the identification of harmful complications, therefore leading to need for more invasive treatment. Case Repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Vanni G. et al [ 29 ] reported a patient who was admitted to the Emergency Department for a worsening dry cough, fever (37.5 °C), chest discomfort, feelings of pressure associated with shortness of breath, fatigue, and slight confusion and had undergone a VABB of the left breast four days earlier as a monitoring measure due to a microcalcification cluster localized at the external-superior quadrant.…”
Section: Discussionmentioning
confidence: 99%
“…Vanni G. et al [ 29 ] reported a patient who was admitted to the Emergency Department for a worsening dry cough, fever (37.5 °C), chest discomfort, feelings of pressure associated with shortness of breath, fatigue, and slight confusion and had undergone a VABB of the left breast four days earlier as a monitoring measure due to a microcalcification cluster localized at the external-superior quadrant.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, the classification of BC molecular subtypes has emerged as a significant breakthrough in tumor assessment and management, providing clinicians with a valuable tool to shift adjuvant treatment decisions from relying solely on statistical risk to incorporating predictive biomarker assessment (5). BC distant disease spread is the result of a not fully understood complex interplay between biological processes, including tumor circulation, proliferation, angiogenesis, and the microenvironment of the target tissue (6)(7)(8). Although progress has been made, many questions remain unsolved in this area (9)(10)(11).…”
mentioning
confidence: 99%